Cultural Identity of Football Supporter Community in Surabaya (Phenomenology Studies of Bonek Campus as a Supporter Community of Persebaya in Surabaya) - Ririn Puspita Tutiasri; Ade Kusuma (Future Science)
Cultural identity refers to the characteristics or sign possessed by a cultured group. Cultural identity will be attached to the identity of members of the cultural group. One of the cultural identity inherent in Surabaya is the term